Analysis of The Application of The Singing Method in Memorizing Vocabulary in The Arabic Language Book Volume 3 for Grade 3 at SDI Amanah Ummah in The Academic Year 2024/2025 - Khoirunnisa Khoirunnisa; Zahrodin Fanani (Jurnal Pendidikan Educandum, 2025)
This study aims to determine the effectiveness of the singing method in helping third-grade elementary students memorize mufrodat (Arabic vocabulary). The research employed a descriptive qualitative approach, focusing on an in-depth understanding of the learning process and students’ responses. The study was conducted at SDI Amanah Ummah Surakarta in the 2024/2025 academic year. Data were collected through observation, structured interviews, and documentation. The findings indicate that the implementation of the singing method, combined with children’s song rhythms, increased students’ enthusiasm and memorization ability of mufrodat. As many as 80% (27 students) were able to fluently recite all the vocabulary taught in a single session, while 13.33% still required repetition, and the remaining 6.67% encountered significant difficulties. In conclusion, the singing method is effective in Arabic language learning for improving elementary students’ vocabulary memorization, although adjustments are still needed to match students’ time management and individual characteristics. This research is expected to serve as a reference for the development of creative learning strategies at the elementary level.